(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Currently universities in accordance with instructions from the Indonesian Ministry of Education and Culture must implement the concept of an independent campus. This study aims to design an OBE curriculum and syllabus information system (Outcome-based Education). to support the concept of an independent campus in Indonesia. The study was conducted using qualitative methods. This research provides benefits fortertiary institutions to implement an independent campus policy in higher education that encourages an increasingly autonomous and flexible learning process so as to encourage the creation of an innovative, non-restraining, and learning culture that is in line with the needs of each tertiary institution.